A Six-Year Retrospective Study of Microbiological Characteristics and Antimicrobial Resistance in Specimens from a Tertiary Hospital’s Surgical Ward - Petros Ioannou; Sofia Maraki; Dimitra Koumaki; Georgios A. Manios; Vasiliki Koumaki; Dimitrios Kassotakis; Georgios V. Zacharopoulos; Diamantis P. Kofteridis; Andreas Manios; Eelco de Bree (Antibiotics, 2023)
Surgery has revolutionized the practice of medicine by allowing the treatment of conditions amenable to conservative medical management with some of them pathophysiologically involving the prevalence of pathogenic microorganisms. On the other hand, infections such as surgical site infections or urinary tract infections may complicate patients hospitalized in surgical wards leading to considerable morbidity, mortality, and increased healthcare-associated costs. The aim of this study was to present the microbiological characteristics and antimicrobial resistance of all isolates identified in microbiological specimens from a surgical ward of a tertiary hospital in Greece during a six-year period. Only specimens that yielded at least one microorganism were included in the analysis. In total, 1459 strains in 789 positive cultures were isolated. The most common sample sent to the microbiology department was pus from surgical wounds. The most common pathogens among all 1459 strains isolated were Enterobacterales at 33% (n = 482), however, the most common genus was Enterococcus at 22.3% (n = 326). Antimicrobial resistance against third-generation cephalosporins was 23% (n = 111/482) among Enterobacterales, while, the rate of vancomycin-resistant enterococci (VRE) was 18.5% (n = 60/324) among Enterococcus species and was increasing in the last years of the study. Antimicrobial resistance of Acinetobacter baumannii to carbapenems was 68.8% (n = 11/16), which was lower than the corresponding rate in other wards in Greece. The antimicrobial resistance rates noted herein raise questions regarding the appropriateness of currently suggested antimicrobials in guidelines and imply that a revision could be required. Practicing clinicians should always be aware of local microbiological data that allow the selection of appropriate antimicrobials for the management of infections. Finally, the increasing rates of VRE noted herein mandate further actions from the point of infection control and antimicrobial stewardship.